Cobalt Nanoparticle-Decorated RuSe2 Nanorods: A Chemical Vapor Deposition Approach for Efficient Electrolytic Hydrogen Evolution - Megersa, Daba Deme; Gudena, Gutema Teshome; Kim, Youngho; Yu, Hak Ki (Crystal Growth and Design, 2024)
Highly stable cobalt nanoparticle-decorated ruthenium diselenide nanorods were grown on carbon paper, resulting in the Co-RuSe2/C structure which was directly utilized as a catalyst for the hydrogen evolution reaction (HER) in an alkaline medium. A reactive chemical vapor deposition (CVD) process with a low temperature, low pressure, and a short reaction time was employed to synthesize the Co-RuSe2/C catalyst. Structural analysis via high-resolution transmission electron microscopy (HRTEM) and elemental distribution using scanning transmission electron microscopy energy-dispersive X-ray spectroscopy (STEM-EDS) confirmed the uniform distribution of cobalt nanoparticles (Co NPs) on densely grown RuSe2 nanorods (NRs). Surface studies using X-ray photoelectron spectroscopy (XPS) revealed the presence of electron-deficient Ru and Se species indicating successful surface electronic structure modification of the Co-RuSe2/C structure. Furthermore, the HER performance of the Co-RuSe2/C catalysts was evaluated in 1 M KOH, demonstrating an excellent performance sustained over an extended period.
Keywords: Alkaline media; Carbon paper; Chemical vapor deposition process; Chemical vapour deposition; Cobalt nanoparticles; Electrolytic hydrogen evolution; Highly stables; Hydrogen evolution reactions; Reactive chemicals; ]+ catalyst